2023
DOI: 10.4018/978-1-6684-6586-8.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Learning Engagement Activities in Promoting Student Interactions and Perceived Online Learning Experience During the COVID-19 Pandemic

Abstract: This chapter explores the use of different synchronous and asynchronous learning engagement support activities to promote student interactions (student-student interaction; student-instructor interaction; and student-content interaction) and provide a better learning experience in an online classroom. These activities included live consultations, online discussion forums, and online formative follow-up quizzes. The findings in this chapter revealed that a well-designed and carefully crafted online course with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies have reported the importance of interactions to promote better student satisfaction in online courses (Bickle et al, 2019;Mc-Cormack, 2010;Moore & Kearsley, 1996;Wong, 2023a;Wong, 2023b). Online courses with high levels of interactivity result in higher levels of student motivation, improved learning and satisfaction compared to online courses with lesser interactive learning activities (Croxton, 2014).…”
Section: Learner Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the importance of interactions to promote better student satisfaction in online courses (Bickle et al, 2019;Mc-Cormack, 2010;Moore & Kearsley, 1996;Wong, 2023a;Wong, 2023b). Online courses with high levels of interactivity result in higher levels of student motivation, improved learning and satisfaction compared to online courses with lesser interactive learning activities (Croxton, 2014).…”
Section: Learner Interactionsmentioning
confidence: 99%
“…Phillips and O'Flaherty (2019) reported the importance of having a competent tutor who is both content-confident and consistent in content delivery as well as trained in using the features available in the virtual classroom to improve student satisfaction with the flipped online nursing course. Recent studies on e-flipped learning show that the eFC is as effective as the traditional one, particularly in improving student satisfaction and perceived learning (Ismail & Abdulla, 2019;Playfoot, 2021;Wong, 2023b).…”
Section: E-flipped Classroommentioning
confidence: 99%